1976
DOI: 10.1901/jeab.1976.26-335
|View full text |Cite
|
Sign up to set email alerts
|

Matching‐based Hedonic Scaling in the Pigeon

Abstract: Four slightly hungry pigeons chose between pairs of grains in a Findley concurrent choice procedure. For Condition I, choice involved hemp versus buckwheat; for Condition II, wheat versus buckwheat; and for Condition III, hemp versus wheat. In all conditions, frequency of reinforcement was arranged according to concurrent variable-interval variableinterval schedules. On the assumption that subjects matched their behavior and time distributions to those of reinforcer value, the choice functions obtained in Cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
125
1
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 31 publications
2
125
1
1
Order By: Relevance
“…Basic research should vary concentrations of sucrose and citric acid solutions parametrically to determine the shape of the functional relation as disparities in reinforcer quality vary. Investigations should extend to different types of reinforcers such as foods and sensory stimulation, with the possible development of hierarchies of momentum and reinforcer quality (see Miller, 1976, for the construction of hedonic scales for types of grain presented in concurrent reinforcement schedules). Applications of reinforcer quality to increase or decrease behavioral persistence should also be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Basic research should vary concentrations of sucrose and citric acid solutions parametrically to determine the shape of the functional relation as disparities in reinforcer quality vary. Investigations should extend to different types of reinforcers such as foods and sensory stimulation, with the possible development of hierarchies of momentum and reinforcer quality (see Miller, 1976, for the construction of hedonic scales for types of grain presented in concurrent reinforcement schedules). Applications of reinforcer quality to increase or decrease behavioral persistence should also be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters SA and Sn represent the subject's sensitivity to variations in reinforcer amount and delay, respectively. (For further examples of multivariate powerlaw transformations of the matching law, see Davison, 1982;Hamblin & Miller, 1977;Hunter & Davison, 1982;Miller, 1976;Schneider, 1973;Todorov, 1973. ) Other researchers (e.g., Green & Snyderman, 1980;Ito & Asaki, 1982) have also discarded a simple multiplicative relationship between amount and delay of reinforcement and have indicated that amount and delay of reinforcement are not linearly equivalent in their effects upon choice.…”
mentioning
confidence: 99%
“…Requests for reprints should be addressed to Leonard Green, Department of Psychology, Washington University, St. Louis, MO 63130. (see Baum, 1979;de Villiers, 1977;Myers & Myers, 1977;Weardon & Burgess, 1982). The matching law has been extended to situations in which qualitatively different reinforcers are delivered from the two alternatives (Hollard & Davison, 1971;Miller, 1976), although an , 'economic, " or behavioral maximization, interpretation has also been proposed (Elsmore, Fletcher, Conrad, & Sodetz, 1980;Hursh & Natelson, 1981;Rachlin, Battalio, Kagel, & Green, 1981). In almost all of the research on matching, however, the responses required to produce reinforcement have been topographically the same on the alternatives (e.g., pecking one of two keys or pressing one of two levers).…”
mentioning
confidence: 99%